Teachers and Students’ Perceptions toward Online English Teaching and Learning during a Covid-19 Pandemic at Senior High School in Torgamba, Labuhanbatu Selatan, Sumatera Utara - Puja Adelia Harahap; Ratmanida Ratmanida (Journal of English Language Teaching, 2021)
This research was aim to analyze how teachers' and students’ perceptions toward online English teaching and learning in the Covid-19 Pandemic. In this research, the researcher used an online questionnaire that consisted of 15 statements for teachers and 27 for students. The participants were 8 English teachers and 140 XI grade students at SMAN 1 and SMAN 2 Torgamba. This study applied a descriptive quantitative design. The findings from the data analysis, most teachers give a positive perception of online English learning with a mean score of 2.57. The process of learning English was easier with online during this pandemic but still, the teachers prefer conventional teaching in the future. Then, most students also give a positive perception of online English teaching and learning with a mean score was 2.54. The process of learning English was easier and could foster students’ independent learning attitudes but still, the students also found some problems in implementing this learning.